Brain magnetic resonance imaging and outcome after hypoxic ischaemic encephalopathy. (3rd March 2016) - Hayes, Breda C.; Ryan, Stephanie; McGarvey, Cliona; Mulvany, Siobhan; Doherty, Elaine; Grehan, Andrea; Madigan, Cathy; Matthews, Tom; King, Mary D.
Abstract: Objective : To correlate pattern of injury on neonatal brain magnetic resonance imaging (MRI) with outcome in infants ≥36 + 0 weeks gestation with hypoxic ischaemic encephalopathy. Methods : Prospective cohort study. Images were blindly reviewed. Children were assessed using a variety of standardised assessments. Results : MRI brain was performed on 88 infants. Follow up was available in 73(83%) infants. Eight of 25(32%) children with normal imaging had below normal assessment scores. Eight infants (12%) had isolated punctate white matter lesions and five of these had abnormal assessment scores. Death and cerebral palsy were seen only in children with imaging scores ≥3 on basal ganglia/thalami (BGT) score or ≥4 on watershed score. No developmental concerns were raised in 3/7(43%) infants with isolated watershed injury. Ten of 13(77%) infants with isolated BGT injury died or developed cerebral palsy. All 23 children with posterior limb of the internal capsule (PLIC) injury displayed developmental difficulties. Conclusions : Almost one-third of infants with a normal MRI brain may be at risk of developmental problems. Punctate foci of white matter injury are common and not always benign. PLIC involvement is usually associated with neurological sequelae including isolated cognitive deficits . Worst outcomes are associated with basal ganglia injury.